Primary pineal malignant melanoma - Oderay Mabel Cedeño Díaz; Roberto Garcia Leal; Cesar La Cruz Pelea (Clinics and Practice, 2011)
Primary pineal malignant melanoma is a rare entity, with only thirteen cases reported in the world literature to date. We report a case of a 70-year-old man, who consulted with gait disturbance of six months duration, associated in the last month with dizziness, visual abnormalities and diplopia. No other additional melanocytic lesions were found elsewhere. The magnetic resonance showed a 25 mm expansive mass in the pineal gland that was associated with hydrocephaly, ventricular and transependimary oedema. The lesion was partially excised by a supracerebellar infratentorial approach. The histological examination revealed a melanoma. The patient received radiation therapy, but died of disease 16 weeks later. We herein review the literature on this rare tumour and comment on its clinical, radiological and histopathological features and differential diagnosis.